Training of educators for personal development of preschooler by means of music arts (Pedagogy of Higher and Secondary Education, 2013)
Belikova O. A. Training of educators for personal development of preschooler by means of music arts.An author exposes the profound component of professional training of future specialists preschool education, taking into account it’s modernization. Speaking to the musical art by means of popularization among the educators of methods and receptions of music therapies, the examples of which are given in the article, an author outlines their influence on development of personality of preschool child.
Keywords: professional training of educator; musical art; musical therapy